Kendala yang Dihadapi oleh Kantor Pertanahan Kota Bandung Sebagai Mediator Para Pihak Dalam Proses Mediasi Penyelesaian Sengketa Batas Tanah - Sukma, Zhilla Permata Radela; Aminah, Aminah (LPPM Universitas Ekasakti Padang, 2024)
Land boundary disputes involve changes in the arrangement of land parcels caused by merging, reducing and separating land parcels that do not correspond to valid data. This problem can be resolved peacefully, but it is not uncommon for certain situations related to land boundaries to cause prolonged tension between the parties. This research aims to explain how the implementation of land boundary dispute resolution through mediation at the Bandung City Land Office and what are the obstacles faced Bandung City Land Office as a mediator for the parties in a mediatiion process for resolving land boundry detemination, thirdly, how the Bandung City Land Office attempts to overcome obstacles in resolving boundary disputes. land through mediation. The research method uses analytical descriptive methods. The approach method used is normative juridical. Data collection techniques, namely literature studies and field studies. Data analysis uses qualitative juridical methods. The results of this research are that the process of resolving land boundary disputes through mediation at the Bandung City Land Office has not been fully implemented in accordance with applicable provisions, namely the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 21 of 2020 concerning Handling and Settlement of Land Cases, because the process is often The mediation carried out did not reach an agreement as explained in Article 1 point 11 of the regulation. In this case, the Bandung City Land Office resolved the dispute that occurred, by deliberation through mediation to find the best solution.